Synthesis of cyclic gem-dinitro compounds via radical nitration of 1, 6-diynes with Fe(NO3)3·9H2O. Issue 19 (2nd May 2019) - Yi, Xiaofei; Chen, Kai; Chen, Wei; Chen, Wanzhi; Liu, Miaochang; Wu, Huayue
Abstract : Cyclic gem -dinitro compounds were obtained via nitration of 1, 6-diynes using Fe(NO3 )3 ·9H2 O as the nitrating agent. Abstract : Cyclic gem -dinitro compounds were obtained via nitration of 1, 6-diynes using Fe(NO3 )3 ·9H2 O as the nitrating agent. The reaction proceeds at room temperature using a cheap nitrating agent. A number of gem -dinitro cyclic compounds were obtained in moderate to good yields. The reaction offers an easy and convenient protocol to prepare gem -dinitro compounds, which are not easily obtained via the known procedures.